Traditional Tibetan medicine: therapeutic potential in rheumatoid arthritis - Yu, Liqiong; Li, Shiling; Pu, Lili; Yang, Chunhong; Shi, Qian; Zhao, Qi; Meniga, Shengbu; Liu, Yue; Zhang, Yi; Lai, Xianrong (Frontiers in Pharmacology, 2022)
Rheumatoid arthritis (RA) is a severe inflammatory autoimmune disease characterized by a failure of spontaneous resolution of inflammation. Inducing immune-regulatory and inflammation resolving pathways represents an effective method to address inflammation in RA. As the oldest medical system in the world, traditional Tibetan medicine (TTM) has been widely used by Tibetan people for the prevention and treatment of RA. This review presents a comprehensive overview of the medicinal plants with anti-RA activity in the traditional Tibetan medical system by searching classic books of Tibetan medicine, drug standards and modern research literatures. A total of 27 species have been found to be effective in treating RA, including Tinospora sinensis (Lour.) Merr., Terminalia chehula Retz., Pterocephalus hookeri (C.B.Clarke) Hoeck. and Aconitum pendulum Busch. Alkaloids, flavonoids, polyphenols and terpenoids were turned out to be the major bioactive components for the remedy of RA. The inhibition of the expression of proinflammatory cytokines by mediating NF-κB, MAPK and JAK/STAT pathways were demonstrated to be the core mechanism for treating RA. In conclusion, the review provides key information and research perspectives for the guidance of further research on anti-RA of TTM.